2012
DOI: 10.1021/ja301174m
|View full text |Cite
|
Sign up to set email alerts
|

Cavitand-Functionalized SWCNTs for N-Methylammonium Detection

Abstract: Single-walled carbon nanotubes (SWCNTs) have been functionalized with highly selective tetraphosphonate cavitand receptors. The binding of charged N-methylammonium species to the functionalized SWCNTs was analyzed by x-ray photoelectron spectroscopy and confirmed by 31P MAS NMR spectroscopy. The cavitand-functionalized SWCNTs were shown to function as chemiresistive sensory materials for the detection of sarcosine and its ethyl ester hydrochloride in water with high selectivity at concentrations as low as 0.02… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 40 publications
1
50
0
Order By: Relevance
“…[7] This high affinity for CO over O 2 of hemoglobin and myoglobin is the underlying mechanism of carbon monoxide poisoning in mammals. [8,9] Although detectors for CO are available, there remains a need for massively [16,17] Theoretical and experimental reports have suggested that CO does not engage in charge transfer with pristine SWCNTs, [18][19][20] indicating the a chemical reactive interface is necessary. Conductivity-based CO detection has been reported for carboxylate-containing, [19] deformed, [21] or doped SWCNTs, [22] as well as SWCNTs dispersed in polymers [23] or decorated with metallic nanoparticles.…”
mentioning
confidence: 99%
“…[7] This high affinity for CO over O 2 of hemoglobin and myoglobin is the underlying mechanism of carbon monoxide poisoning in mammals. [8,9] Although detectors for CO are available, there remains a need for massively [16,17] Theoretical and experimental reports have suggested that CO does not engage in charge transfer with pristine SWCNTs, [18][19][20] indicating the a chemical reactive interface is necessary. Conductivity-based CO detection has been reported for carboxylate-containing, [19] deformed, [21] or doped SWCNTs, [22] as well as SWCNTs dispersed in polymers [23] or decorated with metallic nanoparticles.…”
mentioning
confidence: 99%
“…These coumarin-containing polymers showed moderate solubility in various common organic solvents such as THF, toluene, and CHCl 3 and can solubilize SWNTs in these solvents to different levels. All of the precursors, monomers, and polymers were characterized by 1 H NMR, 13 C NMR, and MS. Physical chemistry properties of the polymers were characterized utilizing UV-vis, TGA, and fluorescence spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] These properties have spawned investigation of SWNTs in a variety of applications, including field-effect transistors (FETs), 10,11 sensors, [12][13][14][15][16] photovoltaics, [17][18][19] flexible printed circuits, 20 touch screens, 21 microelectronic interconnects, 22 and numerous other devices. 23 However, application of these novel nanostructures is often hampered by the heterogeneous character of as-produced SWNT samples.…”
Section: Introductionmentioning
confidence: 99%
“…The peak potential values (E p ) were plotted against the logarithm of the frequencies (log f). A line was fit to the plot and from the plot n was calculated using Equation 12. The Equation giving the line was y = 0.0073x + 0.6938, with R 2 = 0.9967.…”
Section: Electrochemical Studies Of Tetraferrocenyl-cavitand (Cavitanmentioning
confidence: 99%
“…Cavitand-based sensors can operate detecting species being in the gas phase as well as in aqueous solutions [11]. Sarcosine and its ethyl ester hydrochloride in water could be detected with chemiresistor made of carbon nanotubes attached cavitand [12].…”
Section: Introductionmentioning
confidence: 99%